Обзор видов жужелиц подрода Tarsostinus Motschulsky рода Cymindis Latreille (Coleoptera, Carabidae) фауны СССР - Емец, В.М.; Крыжановский, О.Л. (Вестник зоологии, 1973)
The article deals with the characteristic of the subgenus Tarsostinus Mot s c h u i s k y from the genus Cymindis, distribution, synonymy and identification key of 5 species of this subgenus from the USSR. The new species Cymindis (T.) meduedevi Kr y z h a novskij et Emetz sp. n. from the South of the Ukrainian SSR (sandy areas in the Lower Dnieper) is described as well.